Effect of the cooling clothing integrating with phase change material on the thermal comfort of healthcare workers with personal protective equipment during the COVID-19 - Hu, Chenxi; Wang, Zihe; Bo, Renfei; Li, Canyang; Meng, Xi (Case studies in thermal engineering, 2023)
Wearing Personal Protective Equipment (PPE) is essential to protect healthcare workers during the COVID-19, but the traditional cooling methods do not meet the requirements of epidemic prevention during the COVID-19. Therefore, the cooling clothing integrated with phase change material (PCM-CC) was proposed for healthcare workers performing nucleic acid sample collection outdoors. Human experiments and subjective questionnaires were used to test the effect of wearing PCM-CC on the thermal sensations of healthcare workers and to analyze the effectiveness of PCM-CC in relieving thermal stress and thereby, improving the thermal comfort of healthcare workers. Results showed that wearing PCM-CC was effective in alleviating various heat symptoms associated with wearing PPE in a hot-temperature environment. Wearing PCM-CC reduced head and facial discomfort by 25% and 41% under the 26 °C thermal environment, while it improved the mean thermal sensation vote (TSV) values by 0.71 and 1.85 under the 26 °C and 32 °C thermal environments, respectively, and made the mean TSV value close to the neutral value. Meanwhile, wearing PCM-CC reduced mean skin temperatures by 0.65 °C, and the pronounced cooling effect was found in the chest. Wearing PCM-CC could be an effective thermoregulation measure to refine the thermal comfort of healthcare workers during the COVID-19 pandemic.